O świecie koncentracyjnym w literaturze - Mitzner, Piotr; Woroszylski, Wiktor (Colloquia Litteraria, 2020)
Publication of a lecture given by Wiktor Woroszylski in the 1978/79 academic year as part of the Flying University of the Scientific Courses Society. It was an opposition initiative that the Security Service was fighting against. Woroszylski’s lectures concerned the history of Russian and Soviet literature, and the text published here is devoted not only to the labor camps (hence the reference to the work of Michał Heller), but also to broadly understood communist terror.